Nilai-Nilai Nasionalisme Dalam Novel Cut Nyak Dhien Karya M.H. Skelely Lulofs - Yulsafli Yulsafli; Fusrida Fusrida (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
The novel revolves about a woman named Cut Nyak Dhien, who is often called "Cut Nyak". She is a prominent noble lady in Aceh. Her first husband Teuku Ibrahim Lamnga died in the battlefield, the Acehnese call him "Syahid", because he fought in the war with the Dutch Colonials to defend his homeland of Islam. After her husband was martyred in the war with the Dutch, Cut Nyak Dhien remarried with Teuku Umar Djohan Pahlawan. Furthermore, her second husband, Teuku Umar, was also killed by the Dutch. The death of her two beloved husbands added to her hatred to the Dutch Colonials. For Cut Nyak, the Dutch not only had seized her homeland, but also degraded the dignity of the Acehnese, and harassed her religion. The problem of this research is what nationalism values are contained in Cut Nyak Dhien novel, written by M.H. Skelely Lulofs. The source of data of this research is Cut Nyak Dhien novel, written by M.H. Skelely Lulofs. It was published by Bamboo Community in 2007, which consists of 369 pages. The descriptive qualitative method was used for the purpose of this study. Data collection technique was conducted by analyzing the values of nationalism in Cut Nyak Dhien novel written by M.H. Skelely Lulofs. The results of data analysis shows that there are many nationalism values contained in Cut Nyak Dhien novel which are useful for people's lives such as the citizenship value, romantic value, cultural value, state value and religious value.